EVALUATION OF COPPER DEPOSITS PROSPECT IN WAI WAJO AREA OF SIKKA REGENCY, EAST NUSA TENGGARA PROVINCE - Pardiarto, Bambang (Buletin Sumber Daya Geologi, 2014)
Lowo Deba prospect in Sikka Regency, East Nusa Tenggara Province shows significant evidences for copper deposit. The prospect is discovered by joint cooperation activity between Directorate of Mineral Resources Inventory (DMRI) and Korea Resources Corporation (KORES) in the systematic exploration program. The evaluation based on the quantitative analysis of rock and mineral characteristics as well as geologic mapping, petrography, mineragraphy, fluid inclusion, spectra analysis (PIMA), geochemical and geophysical data. The geology of the prospect area consists of Miocene volcanics of Kiro Formation and Tanahau Formation, intrusion of granodiorite and Quaternary volcanics. The volcanic rock shows the characteristic of tholeiitic magma. The predominant system of lineaments in the prospect area tends to be NE-SW trend. This fault structure appears to have closely relationship with the mineralization in Lowo Deba prospect. The mineralization and alteration outcrops appear to be structural controlled to form epithermal deposit type. Most of the mineralizations are hosted by phyllic â argillic altered andesitic to dacitic tuff which is intruded by granodiorite. Rock samples indicate the mineralization type is quartz vein containing chalcopyrite, galena, sphalerite, covellite and pyrite. The best grade revealed from these altered rocks of 6,980 ppm Cu and 50 ppb Au, and from quartz vein of 4,868 ppm Cu and 57 ppb Au. Mineralization stages evolved from initial higher temperatures (> 320Â° C) to later lower temperatures (near 170Â° C).Â Soil geochemical analysis identify two zones of combined anomaly i.e. Au-Cu-Mo and AgPb-Zn. Those anomalies are concentrated in the phyllic and argillic altered andesitic tuff. These soil anomaly coincide with IP anomalies which are found in electrode separation index of n=5 and n=7 in line WA7 with chargeability value up to 405.7 Msec and resistivity value of 37.7 Ohm-m. In general high chargeability and low resistivity anomalies are developed in the direction of southwest to northeast and still open to the northeast. The high chargeability value allows to predict the occurrence of copper deposits potential. Some bore holes are proposed for the next survey to confirm the presence of new copper deposits in the prospect area.